2003
DOI: 10.1007/bf02897938
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic bronchitis-asthma symptoms in biomass fuel exposed females

Abstract: Objectives: We investigated whether exposure to biomass fuel is a potential risk factor for chronic bronchitis and asthma among females in rural area in Van (east Turkey).Methods: The effect of indoor pollution producing various respiratory symptoms was studied in 177 females. Of these, 90 were those who used biomass fuel and 87 were nonusers of biomass fuel. A part of the European Community Respiratory Health Survey quastionnaire and British Medical Research Council questionnaire were used.Results: Asthma rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 19 publications
2
8
0
1
Order By: Relevance
“…As Table shows, asthma was significantly more common in the tandoor‐users group than in the control group. This may be attributed to the detrimental effects of tandoor smoke and is consistent with the findings of earlier studies in which different obstructive lung diseases including asthma were reported to be related to exposure to tandoor smoke . Further, status as an ex‐smoker was also detected more frequently in the tandoor‐users group than in the control group.…”
Section: Discussionsupporting
confidence: 91%
“…As Table shows, asthma was significantly more common in the tandoor‐users group than in the control group. This may be attributed to the detrimental effects of tandoor smoke and is consistent with the findings of earlier studies in which different obstructive lung diseases including asthma were reported to be related to exposure to tandoor smoke . Further, status as an ex‐smoker was also detected more frequently in the tandoor‐users group than in the control group.…”
Section: Discussionsupporting
confidence: 91%
“…Several case-control and cross-sectional studies have evaluated associations between use of biomass fuels and prevalence of asthma with equivocal results among children and women. (3643) Other studies have found strong associations between BMF smoke and COPD among non-smoking women. (9, 20, 44) Important new studies, discussed below, have strengthened the link between TRAP and asthma incidence in children, (30, 4547) incidence in adults (48) and severity in adults.…”
Section: Epidemiology Of Health Effects Of Bmf and Trapmentioning
confidence: 99%
“…Several cross-sectional and case-control studies have shown a high prevalence of chronic bronchitis in populations exposed to biomass smoke. 30,[40][41][42][43][44][45][46][47] One study reported a prevalence as high as 72% in nonsmoking women with more than 10 years of exposure to biomass smoke in rural Pakistan. 46 Another study among Turkish women exposed to biomass smoke showed a prevalence of chronic bronchitis of 58% without significant difference between smokers and nonsmokers.…”
Section: Prevalencementioning
confidence: 99%
“…46 Another study among Turkish women exposed to biomass smoke showed a prevalence of chronic bronchitis of 58% without significant difference between smokers and nonsmokers. 42…”
Section: Prevalencementioning
confidence: 99%